Donor-π-acceptor type porphyrins with large two-photon absorption cross section. (August 2015) - Sheng, Ning; Liu, Dahui; Wu, Jialu; Gu, Bing; Wang, Zhuyuan; Cui, Yiping
Abstract: The third-order nonlinear optical properties of 5-(4-pyrenylalkynylphenyl)-10, 15, 20-tris(4-octyloxyphenyl)porphyrin (1 ) and 5-(4-iodophenyl)-10, 15, 20-tris(4-octyloxyphenyl)porphyrin (2 ) have been comparatively investigated with symmetrical 5, 10, 15, 20-tetra(4-octyloxyphenyl)porphyrin (3 ) and pyrene (4 ) as reference using femtosecond-pulsed Z -scan technique. Due to the D–π–A structure, both A3 B type asymmetric porphyrins1 and2 were revealed to exhibit larger two-photon absorption (2PA) cross sections over the symmetrical analogue3 with the largest value of 6.1 × 10 5 GM revealed for1 because of the intramolecular energy transfer from the excited pyrene moiety to the porphyrin moiety as indicated by the fluorescence spectroscopic result. The good 2PA properties of these A3 B type porphyrins with ultrafast response indicate their good application potential in nonlinear photonic devices. Highlights: Both D-π-A type porphyrins exhibit large 2PA cross sections. The 2PA properties of them were investigated using femtosecond-pulsed Z -scan technique. Intramolecular energy transfer takes place in the newly prepared asymmetric porphyrin.